Global HIV prevention, care and treatment services for children: a cross-sectional survey from the International Epidemiology Databases to Evaluate AIDS (IeDEA) consortium. Issue 3 (13th March 2023) - Vreeman, Rachel C; Yiannoutsos, Constantin T; Yusoff, Nik Khairulddin Nik; Wester, C William; Edmonds, Andrew; Ofner, Susan; Davies, Mary-Ann; Leroy, Valériane; Lumbiganon, Pagakrong; de Menezes Succi, Regina Célia; Twizere, Christella; Brown, Steven; et al.
Abstract : Objectives: To assess access children with HIV have to comprehensive HIV care services, to longitudinally evaluate the implementation and scale-up of services, and to use site services and clinical cohort data to explore whether access to these services influences retention in care. Methods: A cross-sectional standardised survey was completed in 2014–2015 by sites providing paediatric HIV care across regions of the International Epidemiology Databases to Evaluate AIDS (IeDEA) consortium. We developed a comprehensiveness score based on the WHO's nine categories of essential services to categorise sites as 'low' (0–5), 'medium', (6–7) or 'high' (8–9). When available, comprehensiveness scores were compared with scores from a 2009 survey. We used patient-level data with site services to investigate the relationship between the comprehensiveness of services and retention. Results: Survey data from 174 IeDEA sites in 32 countries were analysed. Of the WHO essential services, sites were most likely to offer antiretroviral therapy (ART) provision and counselling (n=173; 99%), co-trimoxazole prophylaxis (168; 97%), prevention of perinatal transmission services (167; 96%), outreach for patient engagement and follow-up (166; 95%), CD4 cell count testing (126; 88%), tuberculosis screening (151; 87%) and select immunisation services (126; 72%). Sites were less likely to offer nutrition/food support (97; 56%), viral load testing (99; 69%) and HIV counselling and testing (69; 40%). 10% of sites rated 'low', 59% 'medium' and 31% 'high' in the comprehensiveness score. The mean comprehensiveness of services score increased significantly from 5.6 in 2009 to 7.3 in 2014 (p<0.001; n=30). Patient-level analysis of lost to follow-up after ART initiation estimated the hazard was highest in sites rated 'low' and lowest in sites rated 'high'. Conclusion: This global assessment suggests the potential care impact of scaling-up and sustaining comprehensive paediatric HIV services. Meeting recommendations for comprehensive HIV services should remain a global priority.